THE ROLE OF FINANCIAL LITERACY, SELF-EFFICACY, AND RELIGIOSITY ON FINANCIAL BEHAVIOR IN THE MODERATION OF SAVING BEHAVIOR - Nur Anisa Dwiyanti; Puji Endah Purnamasari (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
The world of finance is growing. It can bring out consumptive behavior from people and irregular financial management, especially among students. The phenomenon of consumptive behavior among students has encouraged researchers to do research that aims to analyze what factors affect financial behavior. Financial literacy, self-efficacy, religiosity, and saving Behavior on Financial Behavior are the variables used. The research method used is quantitive, with data analysis techniques to test hypotheses using SmartPLS. Data collection by distributing questionnaires via a Google form. The sample obtained for this study amounted to 260 respondents. This research shows that financial literacy, self-efficacy, and religiosity significantly influence financial behavior. This study also proves that saving behavior does not have a moderating effect on financial behavior.